Informal employment in the poor European periphery. Issue 7 (11th July 2017) - Pfau-Effinger, Birgit
Abstract : Purpose: During the transition from socialist to post-socialist regimes, many Central and Eastern Europe societies have developed a broad sector of informal work. This development has caused substantial economic and social problems. The paper aims to discuss these issues. Design/methodology/approach: This paper aims to answer two questions regarding European countries with a relatively weak economy and welfare state: what are the differences in the social characteristics between workers in formal and informal employment? And how might they be explained? According to the main assumption, a key reason why people work in undeclared employment in such countries is that they are in particularly vulnerable positions in the labour market. This paper uses the example of Moldova. The empirical study is based on a unique survey data set from the National Statistical Office of Moldova covering formal and informal employment. Findings: The findings show that, in informal employment, workers in rural areas, workers with a low level of education, young workers and older workers – in the final years of their careers and after the age of retirement – are over-represented. It seems that a significant reason why these workers are often engaged in informal employment is the lack of alternatives in the labour market, particularly in rural areas, compounded by limited social benefits from unemployment benefits and pensions. Originality/value: Research about social differences between workers in formal and informal employment in the countries of the European periphery is rare. This paper makes a new contribution to the theoretical debate and research regarding work in informal employment.